Blunt Abdominal Trauma with Splenic Injury in Uganda: A Case Study - Richard Wismayer (New Advances in Medicine and Medical Science Vol. 2, 2023)
The aim of this study was to report on a case of splenic trauma that presented in a Regional Referral hospital in Uganda and discuss the management of this condition. The spleen is the most commonly injured viscus in blunt abdominal trauma. Abdominal pain with left upper quadrant tenderness or signs of peritonitis in a patient with history of trauma is the most common presentation of this condition. A 43-year-old gentleman was admitted to Masaka Regional Referral Hospital after having been involved in a road traffic accident (RTA). On examination his Glasgow coma score was 15, the airway was intact, his chest was clear and his pulse rate was 120 bpm-1 and blood pressure (BP) 90/60 mmHg. He complained of generalised abdominal pain and nausea.An examination of the abdomen revealed widespread abdominal tenderness, especially in the upper abdomen. He had a 9g/dl haemoglobin level, and the A&E Department’s FAST ultrasound scan revealed fluid in the splenorenal angle. The high incidence of splenic injuries in this age group may be due to high-risk activities at an economically active age. A splenectomy was carried out and there were no other associated injuries of the liver or bowel and other intra-abdominal organs were intact. He had a smooth postoperative recovery and remained hemodynamically stable after surgery. On the fourth post-surgery day, he was let go from the surgical ward. After discharge from the hospital poor follow-up visits is also a concern. Health education programmes in our setting is therefore necessary to prevent post-splenectomy complications in particular post-splenectomy sepsis.